ROLE OF RTDC TO PROMOTE TOURISM IN RAJASTHAN STATE (Phoenix: International Multidisciplinary Research Journal ( Peer reviewed High Impact Journal ), 2023)
The Rajasthan Tourism Development Corporation (RTDC) plays a pivotal role in promoting tourism within the majestic state of Rajasthan, India. This agency serves as the primary vehicle through which the government of Rajasthan facilitates and enhances the tourism sector, thereby contributing to economic growth and cultural preservation. This abstract will delve into the multifaceted role of RTDC in promoting tourism in Rajasthan, highlighting its initiatives, strategies, and their impact on the state's tourism landscape.